The Effect of Agency Conflict, Dividend Policy and Growth Opportunity as Moderating Variabel on Firm Value - erfiana, deka; Ardiansari, Anindya (Universitas Negeri Semarang, 2016)
This study aims to investigate the effect of agency conflict on dividend policy (Dividend Payout Ratio), dividend policy and growth opportunity on firm value, and analyzing growth opportunity moderate the effect of dividend policy on firm value. The population are 72 manufacturing companies which is listed on Indonesia Stock Exchange (IDX) from 2012 until 2014. The sample are 24 companies using purposive sampling technique. The analysis method in this study is a simple regression analysis and multiple regression analysis and Moderated Regression Analysis (MRA) to examine the effect of moderating variable. Firm value variable is proxied by Price Book Value (PBV), Agency conflict variable is proxied by Total Asset Turnover (TAT), dividend policy variable is proxied by Dividend Payout Ratio (DPR), and growth opportunity is proxied by the precentage of changes in total assets.The result show that agency conflict has positive significant effect on dividend policy, dividend policy has positive significant effect on firm value, growth opportunity has no significant effect on firm value, and growth opportunity as moderating variable can effect the relationship of dividend policy and firm value.